Quantificação volumétrica do rebordo alveolar após reanatomização do assoalho do seio maxilar para instalação de implantes - Oliveira, Eduardo de (2021)
Background: The loss of upper posterior teeth leads to bone resorption and maxillary sinus pneumatization, often preventing immediate insertion of dental implants and leading to the need for sinus floor augmentation (SFA) and bone graft. Objective: To evaluate, in cone-beam computed tomography (CBCT) images, the volumetric changes in the alveolar ridge and maxillary sinus after bone grafting for SFA and dental implants placement. Materials and methods: Bone and sinus volume of 16 maxillary sinuses of 12 patients submitted to SFA, bone graft, and implant placement were evaluated. CBCT exams were performed three times: evaluation of the residual bone (T0), evaluation of the graft after SFA before implant surgical planning (T1), and evaluation after implants healing (T2). All DICOM formatted images were evaluated by two calibrated examiners (ICC > 0.9) using ITK-SNAP software. The volume measured at each time point was compared using the ANOVA test. Clinical and demographic variables were collected and the percentage of bone gain and resorption were compared using the t-test. The significance level considered was P < 0.05. Results: The bone volume showed a significant increase after SFA (T1), with also significant resorption (T2); the sinus volume showed a significant reduction after SFA (T1) but with volume maintenance over time (T2). Sites with volumetric variation at T1 greater than 200% had lower longitudinal resorption (p=0.036), with no association with clinical or demographic variables (p > 0.05). Conclusion: The present study found an average increase of 200% in the bone ridge after SFA and an average resorption of 11% over four years, after implant placement, concentrated in the cervical region of the implants. Bone gain and resorption of the graft volume were not associated with the clinical or demographic variables of the patients.